Bandung And Kawasaki: A Partnership In Environmental Issue - Hakiem, Fadhlan Nur; Argenti, Gili; Gustianti, Nurbani Adine (Universitas Riau Kepulauan, 2025)
This research aims at analysing the strategic role of international cooperation by local governments in addressing environmental issues in urban areas, focusing on the collaboration between Bandung and Kawasaki since 2016. Both cities have agreed to cooperate in the environmental sector, particularly in water management, air quality control, and waste management. The research employed qualitative research, with data collected through interviews and literature reviews. The data analysis process involved data reduction, presentation, and conclusion drawing. The theories and concepts applied in this research were city diplomacy and city networks. The results shows that the partnership between Bandung and Kawasaki has played an important role in strengthening the capacity of Bandung’s civil servants to address environmental challenges. By learning from Kawasaki’s experience through technology and knowledge transfer, Bandung has been able to develop more structured and systematic environmental policies. However, the direct impact of this partnership on the local community remains limited. Challenges such as bureaucratic complexities, leadership changes that shift policy priorities, and budget constraints have slowed down the implementation of program. On a broader level, this research contributes to the understanding of city diplomacy and international city networks, demonstrating how partnership can be valuable strategy for addressing environmental issues. From a practical standpoint, the findings highlight the need for stronger cross-sector coordination, more flexible bureaucratic processes, and better communication strategies to engage the local community in environmental initiatives.